Gemcitabine and Cisplatin Combination Chemotherapy in Triple Negative Metastatic Breast Cancer Previously Treated with a Taxane/Anthracycline Chemotherapy; Multicenter Experience - DANE, FAYSAL (AEPRESS SRO, 2012)
This study was aimed to establish clinical efficacy and tolerability of gemcitabine and cisplatin combination in patients with metastatic triple negative breast cancer progressing after anthracycline and taxane based chemotherapies. Thirty-three patients who were given cisplatin and gemcitabine for triple negative and metastatic breast cancer were evaluated retrospectively. A total of 141 cycles were administered with a median 4 cycles per patient. Median follow-up time was 14 months (range, 2-36 months). Objective response rate was 27.3%. Total clinical benefit of the combination was 48.4%. The estimated median progression free survival and median overall survival were 5 months and 14 months, respectively. The most common Grade 3 and 4 toxicity were neutropenia and thrombocytopenia observed in 10 (27.7%) and 9 (24.9%) patients, respectively. The combination of the gemcitabine and cisplatin after taxane/anthracycline is well tolerated and seems to be effective with acceptable toxicity profile.
Keywords: Triple negative; metastatic breast cancer; cisplatin; gemcitabine; EFFICACY